JPSS-3 / 4 VIIRS response versus scan angle characterization and performance - McIntire, Jeff; Moyer, David; Angal, Amit; Xiong, Xiaoxiong (Frontiers in Remote Sensing, 2023)
Scientific studies of the Earth's climate increasingly rely on high quality satellite observations. The Visible Infrared Imaging Radiometer Suite (VIIRS) is a key sensor onboard a series of satellites [Suomi National Polar-orbiting Partnership (SNPP) and Joint Polar-orbiting Satellite System 1 -4 (JPSS-1 -JPSS-4)] that generates scientific data from land, ocean, and atmosphere used in these climate models. Providing quality scientific data from space-borne sensors requires the instruments to be well calibrated. While much of the calibration can be maintained on-orbit, some aspects of the calibration can only be measured prior to launch. One VIIRS parameter that needs to be measured pre-launch is the response versus scan angle (RVS). The RVS measures the relative change in the reflectance of the scanning optics as a function of angle of incidence. With the RVS, the gain calibration measured on-orbit can be transferred to any scan angle. The JPSS-3 and JPSS-4 instruments have undergone ground testing including the RVS measurements. The characterization of both instruments' RVS is the subject of this work. Results indicate that the measurements are comparable to previous VIIRS builds and are expected to contribute to the generation of high quality science data once JPSS-3 and JPSS-4 are on-orbit.